Analisis Penyebab Terjadinya Blackout pada KM. Dharma Kartika IX saat Bermanuver - Saputra, Muhammad Sa’id Agil; Wiweko, Albert; Siregar, Muhammad Sapril (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
A blackout on a ship is a condition where the main propulsion power source on the ship does not operate due to the lack of electrical supply from the diesel generator, which serves as the primary source of electricity on the ship. Ship maneuvering, on the other hand, refers to the ability to turn and pivot while sailing. This ability is crucial for the safety of the ship, especially when operating in restricted waters or near ports. The blackout occurs as a result of generator overload or the inability of an electrical voltage and current to flow too high or too large. The load is too high because the bow thruster consumes too much electrical voltage. In fact, on KM. Dharma Kartika IX, the generator has already supplied a significant amount of electricity to various parts of the ship, including the lighting system throughout the ship, from the mast to deck 3, the cooling system, and several navigation systems. The aim of this research is to understand and explain the causes of blackouts in the electrical system of KM Dharma Kartika IX during maneuvering and to find solutions that should be implemented in case of problems with the generator unit. The method I used to gather this data is through direct observation during seagoing service on the subjects under examination.